Fostering Critical Thinking in Early Childhood: An Experimental Study on Loose Parts Media in Kindergarten - Astri Purwanti; Rakimahwati Rakimahwati; Farida Mayar; Setiyo Utoyo (AL-ISHLAH: Jurnal Pendidikan, 2025)
Critical thinking, a higher-order cognitive skill, is essential in forming reliable decisions. In early childhood education, integrating developmentally appropriate methods such as Loose Parts play has the potential to foster creativity and critical thinking. This study explores the impact of Loose Parts media on the critical thinking abilities of children aged 5–6 years at Tunas Harapan Kindergarten, Tambang District, Kampar Regency. A quasi-experimental design with a pretest-posttest control group structure was employed. The sample consisted of 20 children divided equally into an experimental group (n=10) and a control group (n=10). The experimental group engaged in activities involving Loose Parts, while the control group followed conventional methods. Critical thinking skills were assessed before and after the intervention. Analysis using ANOVA revealed a significant improvement in the critical thinking skills of the experimental group. The calculated F-value was 6.122, with a significance value of 0.024 (df = 1, α = 0.05). These results indicate a statistically significant effect of Loose Parts media on the development of critical thinking. The findings support the hypothesis that Loose Parts play promotes critical thinking in early learners. The significant difference observed highlights the potential of this approach as an effective educational strategy in early childhood development.